Understadning Faraid: the Case of University Students - Abdelghani Echchabi; Osman Sayid Hassan Musse (Global Review of Islamic Economics and Business, 2014)
The purpose of the study is threefold (1) to examine the level of faraid awareness among university students, as well as (2)the factors that may influence it, and (3)to investigate whether there is any difference between the various groups of respondents based on gender, education level, age and country of origin. The study uses three main statistical techniques to analyse the data, namely, one sample t-test, MANOVA and multiple regression. The data was gathered by distributing the questionnaire to 150 students of International Islamic University Malaysia. The findings indicate that overall the students have good knowledge about faraid. Nevertheless, the students were found to have a misconception and misunderstanding regarding female share in inheritance in Islam. In addition, the findings show that there is significant education level difference in faraid awareness. Finally, the findings conclude that among the variables initially included in the study, only facilitating conditions is significantly influencing the level of awareness of the university students.